Microlearning Pelaporan Keuangan UMKM Pemula di Kota Jayapura - Neni Setiarini; Isma Shalihi Ahlia; Fanny K Sitompul; Aprianto La'lang Kuddy; Palti Maretto Caesar Manalu (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aimed to improve the financial reporting competency of early-stage SME owners in Jayapura through a microlearning-based training approach. A total of 40 participants were selected through online registration. The program was structured in three stages: preparation, implementation, and evaluation. Results indicated a significant increase in participant knowledge: the average pre-test score was 37.8%, rising to 88.5% in the post-test, 50.7 percentage point improvement. The greatest gain was observed in understanding of balance sheet concepts (+65 percentage points). Participants reported heightened confidence in preparing basic financial records independently. The findings confirm that microlearning, which structures content into focused 3–5 minute units, is highly effective for time-constrained SME practitioners. This activity aligns with SDG Goal 8 (Decent Work and Economic Growth) and Goal 9 (Industry, Innovation, and Infrastructure)